2020
DOI: 10.1371/journal.pone.0241122
|View full text |Cite
|
Sign up to set email alerts
|

Dichloroacetate-induced metabolic reprogramming improves lifespan in a Drosophila model of surviving sepsis

Abstract: Sepsis is the leading cause of death in hospitalized patients and beyond the hospital stay and these long-term sequelae are due in part to unresolved inflammation. Metabolic shift from oxidative phosphorylation to aerobic glycolysis links metabolism to inflammation and such a shift is commonly observed in sepsis under normoxic conditions. By shifting the metabolic state from aerobic glycolysis to oxidative phosphorylation, we hypothesized it would reverse unresolved inflammation and subsequently improve outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 67 publications
(103 reference statements)
0
7
0
Order By: Relevance
“…In particular, the metabolic shift may be an attractive target for nonhormone-based endometriosis treatment. Treatment strategies that utilize metabolic reprogramming are implemented not only in cancer but also in sepsis ( Bakalov et al 2020 ), schizophrenia ( Pruett & Meador-Woodruff 2020 ), autoimmune disease ( Kornberg 2020 ), or mitochondrial disease ( Kobayashi et al 2021 a ).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the metabolic shift may be an attractive target for nonhormone-based endometriosis treatment. Treatment strategies that utilize metabolic reprogramming are implemented not only in cancer but also in sepsis ( Bakalov et al 2020 ), schizophrenia ( Pruett & Meador-Woodruff 2020 ), autoimmune disease ( Kornberg 2020 ), or mitochondrial disease ( Kobayashi et al 2021 a ).…”
Section: Resultsmentioning
confidence: 99%
“…The expression levels of hexokinase 2 (HK2)—which catalyzes the first step of glycolysis [ 32 ]—and pyruvate kinase muscle form 2 (PKM2)—which catalyzes the last step of glycolysis [ 33 ]—increased in LTZ-rats compared to those in Veh-rats (HK2, 1.82-fold, p < 0.05) (PKM2, 1.42-fold, p < 0.05) ( Figure 4 A). Additionally, the expression of pyruvate dehydrogenase (PDH)—the enzyme that converts pyruvate to acetyl-CoA [ 34 , 35 ]—also increased in LTZ-rats compared to Veh-rats (2.03-fold, p < 0.05) ( Figure 4 A). From an in vitro assay using the H9c2 cell line, the expression levels of HK2, PKM2, and PDH were found to be higher in LTZ-cells compared to those in Veh-cells (HK2, 2.00-fold, p < 0.05) (PKM2, 1.24-fold, p < 0.05) (PDH, 1.86-fold, p < 0.05) ( Figure 4 B).…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, PDHC is a critical regulator of lactate levels. Bakalov et al ( 20 ) confirmed that sepsis could lead to decreased PDHC activity and increased lactic acid levels in the gross tissues of Drosophila, while the upregulation of PDHC activity could reduce lactic acid levels and improve the survival rate of the flies. In a rat model of sepsis, inhibiting PDHC activity can lead to a significant increase in the level of lactate, illustrating the negative regulatory effect exerted by PDHC activity on the level of lactic acid ( 37 ).…”
Section: Pathological Effect Caused By Pdh Imbalancementioning
confidence: 99%
“…This finding highlights that PDK inhibition exerts positive regulatory effects in glycolysis via PDHC, allowing M1 macrophages to be polarized toward the M2 phenotype, thus tempering the release of inflammatory mediators ( 42 ). Bakalov et al showed that PDHC activation led to the lowered level of cecropin-A and defensin, two releasing markers of pro-inflammatory factors, resulting in the improvement of life span of septic Drosophila ( 20 ). These results indicate that regulation of PDHC activity may represent a therapeutic target in the treatment of sepsis.…”
Section: Pathological Effect Caused By Pdh Imbalancementioning
confidence: 99%
See 1 more Smart Citation